Recent development of graphene oxide-based membranes for oil–water separation: A review - Junaidi, Nurul Fattin Diana (Elsevier B.V., 2021)
Separation of oil in water emulsion remains as a critical issue due to the high volume of oily wastewater discharged by industrial processes. Membrane technology has a great industrial interest for this oil–water separation owing to its simple operational process and high separation efficiency. However, the hydrophobicity properties of membrane can aid the membrane fouling phenomenon and shorten the life of membranes. As a result, modification of membranes, particularly on hydrophilicity enhancement, is required to optimise the membrane performances. Over the years, graphene and its derivatives, particularly graphene oxide (GO) have gained great research interest in the field of membrane for water and wastewater treatment due to its ultimate thinness and unique layered structure. These features enhance the permeation fluxes, increase hydrophilic property, improve physicochemical properties and provides rich oxygen-containing groups for further modification, making it excellent for ionic/molecular separation. This review article discusses the recent progress of GO-based membranes through various configurations, i.e., free-standing, supported, and polymer nanocomposite for oil–water separation. The advancements of using GO for membrane morphology alteration, fouling mitigations as well as mechanical strength are discussed. The key issues for the development of high-performance GO membranes and prospects for imminent research are highlighted.